The Effect of a Skills-Based Behavioral Program on Raising the Self-Concept of Individuals with Mild Intellectual Disability in UAE - Almheiri, Ousha (Journal of the American Academy of Special Education Professionals, 2018)
This study aimed at examining the effect of a behavioral program on raising the level of self-concept among individuals with mild intellectual disability. To achieve this goal, the researcher prepared a skills-based behavioral training program that is geared towards individuals with mild intellectual disability. Subjects were assigned randomly in groups (experimental and control). The results indicate that there were significant differences between the two groups in favor of the experimental group.